Battle Reading the Russian Pacific Fleet 2023 - 2030 - Muraviev, Alexey (Sea Power Centre Australia Department of Defence, 2023)
On 21 May 2023, the Red Banner Russian Pacific Fleet (RUSPAC) marked its 292nd anniversary. Russian naval presence in the Pacific maritime theatre dates back to 1731, when the country formally established its first naval footprint on the shores of the Pacific Ocean.